PEMANFAATAN NORMALIZED GREEN RED DIFFERENCE INDEX (NGRDI) UNTUK MENDUGA KADAR N-TOTAL PADA LAHAN PADI DI KABUPATEN PAMEKASAN - Zuelfiekar Akmil Rida; Kurniawan Sigit Wicaksono (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Inefficient fertilization is the cause of decreased rice production. This is due to the inappropriate use of fertilizers. The absence of information on soil nitrogen content in their area causes farmers not to apply fertilizer properly. Analysis of soil nitrogen content in Pamekasan Regency requires much time, cost, and effort. Remote sensing methods can be used to obtain information on soil nitrogen levels by reducing the number of samples used. This study aims to estimate nitrogen content in rice fields using the vegetation index in the form of NGRDI (Normalized Green Red Difference Index). This research was conducted by purposive random sampling method based on 40 land map units formed in Pamekasan Regency, laboratory analysis, statistical analysis, and making distribution maps. The results showed that there was a significant relationship between the NGRDI pixel value and the nitrogen content, with a correlation value of -0.42. The regression equation results obtained from the NGRDI value with nitrogen content are y = -0.269x + 0.139. The accuracy test was carried out by the RMSE method, and the result was 0.027. This shows that the NGRDI index can estimate soil nitrogen content in Pamekasan Regency